META ANALYSIS ON THE APPLIED OF PROBLEM BASED LEARNING IN JUNIOR HIGH SCHOOL STUNDENTS TO THE SCIENCE LEARNING OUTCOMES - Wulandari, Wulandari; Zahra, Firda Az; Yurnetti, Yurnetti; Muttaqiin, Arief (Department of Science Education, 2025)
In the 21st century the educational curriculum has developed to a higher level with the aim of building students' intelligence abilities in learning, especially in science learning, one way to improve students' cognitive learning outcomes is to use Problem Based Learning (PBL) models. PBL is a learning model that requires students to be able to solve problems that occur in the real world as a context for developing critical thinking skills and problem solving. The PBL learning model has been widely used by previous researchers, but not many studies have thoroughly examined the PBL model in junior high school science learning. The method used in this research is descriptive using a quantitative approach followed by meta-analysis techniques. The population in this study were S1-S3 indexed scientific publication articles and articles with ISSN, the sample used in this study were 31 articles. There are three results from this study, firstly the application of the PBL model in science learning has a very high influence on class VII with an effect size of 1,32, secondly the application of the PBL model has a very high influence on the material growth and development of living things with an effect size value of 4,27, the third application of the PBL model to students' cognitive learning outcomes has a very high effect with an effect size value of 1,19.